2017
DOI: 10.1111/ijpp.12349
|View full text |Cite
|
Sign up to set email alerts
|

What can community pharmacy learn from the experiences of transition to practice for novice doctors and nurses? A narrative review

Abstract: Objectives In the absence of literature reporting the transition experiences of novice community pharmacists, peer-reviewed evidence on the transition experiences of novice doctors and nurses was identified and reviewed. Specific objectives included identifying the challenges to transition and their perceived impact, before considering the implications for novice community pharmacists. Methods The electronic databases MEDLINE, EMBASE, CINAHL, PsycINFO and ScienceDirect were searched for full peer-reviewed orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
(237 reference statements)
0
12
0
Order By: Relevance
“…The problem occurs when these internal divisions are visible at national level reducing a profession's ability to bargain with the State affecting its reprofessionalisation efforts . Larson speculates that professional socialisation fosters ideological solidarity and improves professional cohesion, which can be achieved in pharmacy through embedding a formal postgraduate clinical career pathway with additional relevant training that is represented in practice …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem occurs when these internal divisions are visible at national level reducing a profession's ability to bargain with the State affecting its reprofessionalisation efforts . Larson speculates that professional socialisation fosters ideological solidarity and improves professional cohesion, which can be achieved in pharmacy through embedding a formal postgraduate clinical career pathway with additional relevant training that is represented in practice …”
Section: Discussionmentioning
confidence: 99%
“…[11,26,27,46] Larson speculates that professional socialisation fosters ideological solidarity and improves professional cohesion, which can be achieved in pharmacy through embedding a formal postgraduate clinical career pathway with additional relevant training that is represented in practice. [12,57]…”
Section: Intraprofessional Divisions In Pharmacymentioning
confidence: 99%
“…In addition, inappropriate planning and maintenance of the health workforce can lead to wastage of precious resources . Research in health workforce has sought to inform decision‐making though is necessarily broad to include, for example, issues around needs assessment, migration patterns, sector monitoring, retention, representation, trainee intentions post‐qualification,brain‐drain’ and task‐shifting . Health workforce observatories can also play a role in mapping educational opportunities, understanding of workforce supply, describing specific settings or countries that can inform health strategy and policy, and quantifying staffing needs in specific settings .…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review (Magola, Willis, & Schafheutle, ) exploring transitions of novice nurses and doctors found that they experienced challenges [or stressors] when they interacted with the workplace environment and reacted to their new roles, as proposed by Meleis' transition theory (Meleis et al, ). In this review, challenges associated with transition were categorised as personal, social, or job related (Magola et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review (Magola, Willis, & Schafheutle, ) exploring transitions of novice nurses and doctors found that they experienced challenges [or stressors] when they interacted with the workplace environment and reacted to their new roles, as proposed by Meleis' transition theory (Meleis et al, ). In this review, challenges associated with transition were categorised as personal, social, or job related (Magola et al, ). Personal challenges described the novice's response to their role (psychological pressure, cognitive impairment, emotional, or intellectual stress), social challenges resulted from workplace relationships (interpersonal/interprofessional conflict, fitting in or mismatched expectations) and job‐related challenges resulted from role demands (shift patterns, responsibility for complex patients, rotation, or time constraints).…”
Section: Introductionmentioning
confidence: 99%